Rab GTPases regulate the trafficking of channels and transporters - a focus on cystic fibrosis - Farinha, Carlos (2018)
The amount of ion channels and transporters present at the plasma membrane is a crucial component of the overall regulation of ion transport. The number of channels present result from an intricate network of proteins that controls the late events of channel trafficking, such as endocytosis, recycling and targeting to lysosomal degradation. Small GTPases of the Rab family are key players in these processes thus contributing to regulation of fluid secretion and ion homeostasis. In epithelia, this involves mainly the balance between the chloride channel CFTR and the sodium channel ENaC, whose misfunction is a hallmark of cystic fibrosis - the commonest recessive disorder in Caucasians. Here, we review the role of GTPases in regulating trafficking of ion channels and transporters, comparing what is known for CFTR and ENaC with other types of channels. We also discuss how feasible would be to target the Rab machinery to handle a disorder such as CF.